The Miltonic Sensorium - Gabel, Tobias (Universitätsverlag Winter, 2022)
Over the long reception history of the Miltonic corpus, Milton’s treatment of sensory perception, as well as the sensory qualities (or lack thereof) observable in his poetry and prose, have given rise to often heated debate. Combining recent scholarship in the field of sensory studies with a conceptual-metaphor approach, this study proposes a new angle on Milton and the senses, arguing for the central importance of “sensory discourse” in both his poetry and prose, situating the author’s approach to perception in its early modern context, and highlighting throughout the interlocking claims to experiential knowledge and poetic merit that characterize sensory discourse in Milton. A particular focus is on Milton’s earliest poetry and prose – his Latin elegies and ‘prolusiones’ – as well as on the four proems to ‘Paradise Lost’.
9783825372026
Keywords: Hochschulschrift; Literaturwissenschaft: Prosa; Erzählung; Roman; Autoren; Abendländische Philosophie: Aufklärung; Philosophie: Epistemologie und Erkenntnistheorie; Literaturwissenschaft: Lyrik und Dichter; Vereinigtes Königreich; Großbritannien; Englisch; 17. Jahrhundert (1600 bis 1699 n. Chr.); Milton; John; Borges; Jorge Luis; Sinneswahrnehmung; englische Literatur; 17. Jahrhundert; Epistemologie; Perzeption; Wahrnehmung; Sensory Studies; Frühe Neuzeit; Metapher; Philosophie